The Influence of self-efficacy, work discipline, and compensation on employee performance through work motivation in textile and garment companies in West Java - Sjarifudin, Didin; Widyastuti, Tri; Renwarin, Joseph MJ; Suroso, Sugeng (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to examine the influence of self-efficacy, work discipline, and compensation on employee performance through work motivation in textile and garment companies in West Java. Methodology/approach: This study uses a descriptive quantitative approach with 370 respondents from an unknown population. Data were analyzed using SmartPLS through validity and reliability tests, inner and outer model evaluations, and hypothesis testing to ensure accuracy and reliability of findings. Results/findings: 1) Self-efficacy has a positive and significant effect on motivation; 2) Work discipline has no effect and is not significant on motivation; 3) Compensation has no effect and is not significant on motivation; 4) Self-efficacy has a positive and significant effect on employee performance; 5) Work discipline has a positive and significant effect on employee performance; 6) Compensation has a positive and significant effect on employee performance; 7) Motivation has a positive and significant effect on employee performance; 8) Self-efficacy has a positive and significant effect on employee performance through motivation; 9) Work discipline does not have a positive and significant effect on employee performance through motivation; and 10) Compensation does not have a positive and significant effect on employee performance through motivation. Conclusions: The study reveals that self-efficacy significantly enhances work motivation and performance, with motivation mediating this effect. Work discipline improves performance but not motivation, while compensation has no significant influence. Only self-efficacy indirectly boosts performance through motivation, highlighting motivation’s pivotal role in driving employee effectiveness and productivity. Limitations: This study is limited to Employee Performance and Work Motivation. Contribution: This study contributes to the understanding of factors that influence employee performance, focusing on factors such as self-efficacy, work discipline, compensation, and work motivation.